METHODICAL PROBLEM IN THE RESEARCHES OF EDUCATIONAL HISTORY - Hüseyin ŞİMŞEK (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The main aim of this study is to attract attention to the methodical problem in research of educational history. Method, is a way that must be pursued for scientific researches. Educational researches which are the sub-field of history researches, are considered in the qualitative part of researches. Study comes into being from two main part. The first part includes theoretical knowledges related to the researches of history and educational history and the second part includes a conceptual framework related to qualitative method which is used in the researches of educational researches